Searching for Boko Haram: a history of violence in Central Africa - MacEachern, Scott (Oxford University Press, 2018)
Introduction -- Deep time, modern consequences -- Frontiers : mountains and plains -- States, frontiers and enslavement -- Kalashnikovs, cell phones and motorcycles -- Placing Boko Haram -- Pasts, parallels and the future -- Reprise: timescales -- Reprise: states, people and violence -- Reprise: Boko Haram on the borders -- Songs of smugglers and bandits -- The future